IMPROVING THE EFFECTIVENESS OF LEARNING MILITARY CONCEPTS THROUGH INTERACTIVE METHODS - Tavakalov Alisher Akbaralievich (Journals Park Publishing, 2022)
The information and knowledge accumulated by mankind over the centuries should be assimilated and enriched by each new generation and serve the development of society. The acquisition of accumulated information and knowledge is a very complex process and should be organized only on a scientific basis. But every process is a social phenomenon. Therefore, it has its own rules and characteristics. The didactic department of pedagogy deals with the study, analysis of the rules of the educational process and the search for new areas of knowledge, the development of effective methods of their acquisition. Philosophy, psychology, and physiology also study the educational process, human cognition, and the phenomena of thinking. However, didactics approaches these issues as a specialized science and conducts research. Didactics deals with all aspects of education, its organization, acquisition of knowledge, definition of the content of education, methods and rules of teaching.
Keywords: Methodological help; textbooks; teacher